Hubungan Dukungan Sosial Teman Sebaya dengan Harga Diri (Self-Esteem) Remaja di SMA Negeri 1 Kubung - Savira, Meri Devi Devi; Sukmawati, Indah (Current Issues in Counseling, 2023)
This research is motivated by the existence of adolescents who view themselves negatively so that adolescents have low self-esteem. One of the factors thought to influence self-esteem is the social support of peers. This study aims to: (1) describe the self-esteem of adolescents in SMA Negeri 1 Kubung, (2) describe the social support of adolescent peers in SMA Negeri 1 Kubung, (3) test whether there is a relationship between peer social support with self-esteem adolescents in SMA Negeri 1 Kubung. The type of research used is correlational descriptive quantitative. The research sample consisted of 289 teenagers at SMA Negeri 1 Kubung using a proportionate stratified random sampling technique. The instruments used are the Likert Scale and Guttman Scale models. Data were analyzed using descriptive analysis techniques and Pearson Product Moment. The results of the study revealed that: (1) peer social support for teenagers in SMA Negeri 1 Kubung was in the medium category, (2) self-esteem for teenagers in SMA Negeri 1 Kubung was in the low category, (3) there was a positive relationship significant relationship between peer social support and adolescent self-esteem at SMA Negeri 1 Kubung with r = 0.415